Integration of scRNA-seq and ST-seq identifies hyperproliferative RRM2+ cells features and therapeutic targets in gastric cancer - Shuai Ping; Xiong Jia; Yanan Tian (Journal of Translational Medicine)
Abstract Background Despite substantial progress in discovering novel therapeutic targets and compounds, cancer hyperproliferative cells (CHCs) play a central role in driving tumor progression in gastric cancer (GC). High-resolution single-cell RNA sequencing (scRNA-seq) integrated with spatial transcriptomics sequencing (ST-seq) elucidating the role of the CHC microenvironment in driving GC progression remains lacking. Methods Through integrated analysis of 40 scRNA-seq samples and 6 ST samples from human gastric tissues spanning tumor progression, we delineate the phenotypic plasticity of tumor epithelium and characterize the transcriptional trajectory from normal gastric cells to CHCs, a process associated with RRM2 overexpression. Finally, we validated the analysis results through cellular and animal experiments. Results Our findings demonstrate that RRM2 knockdown triggers ferroptosis in GC cells by promoting lipid peroxidation and intracellular iron accumulation. We further screen a compound and RRM2 inhibitor, osalmid, which effectively suppresses tumor growth in GC cell xenografts by triggering ferroptosis, thus offering a new therapeutic option for GC. Conclusions This study elucidates the critical role of RRM2 + CHCs in gastric cancer development and progression, providing novel insights for targeted therapies. The discovery of osalmid as a potential therapeutic agent offers a promising new treatment strategy for GC.